Three-Phase Power Flow Tool for Electric Distribution Grids: A Julia Implementation for Electrical Engineering Students - Montoya, Oscar Danilo; Garcés-Ruiz, Alejandro; Gil-González, Walter (Ingeniería, 2023)
Most of the concepts involved in Electrical Engineering have been developed from the 20th century to the present day. One of the most popular studies in this field is the power flow problem for electrical systems composed of multiple nonlinear loads (i.e., loads with constant power consumption) [1].